Determination of exchange coupling constants in linear polyradicals by means of local spins - Oña, Ofelia Beatriz (2017)
This work extends the previously reported studies (Oliva et al. in Theor Chem Acc 132:1329, 2013, Theor Chem Acc 134:9, 2015) on electronic structures of simple polyhedral polyradicals constructed from s = ½ closo-carborane CB11H12 • structural units. Linear polyradical structures obtained from these units connected by means of –CH2– bridges are described in terms of their energies and local spins. The resulting spin states of these chains have been mapped onto a phenomenological Heisenberg spin Hamiltonian, providing the evaluation of spin exchange coupling constants and performing an analysis of their transferability. The eigenvalues of this Hamiltonian allow one to determine the ground spin state and the suitable combinations of spin orientations of the magnetic sites. We prove that the minimal energy in all these systems corresponds to the highest-spin state.